Deteksi Jumlah Bakteri Total dan Coliform pada Sludge dari Proses Pembentukan Biogas Campuran Feses Sapi Potong dan Feses Kuda - Benito, Tubagus; Hidayati, Yuli Astuti; Rusdi, Udju D; Marlina, Eulis Tanti (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
This study aims to determine the amount of total and coliform bacteria in sludge from the process of forming  a mixture  of  biogas  feces  of  beef  cattle  and  horse  feces. The method  used  in  this  study  is  the experimental method in the laboratory using a completely randomized design with 3 treatments, ie P1 = C  / N  ratio  of  25,  P2  = C  / N  ratio  of  30  and  P3 = C  / N  ratio  of  35  and  replications  6  times.  To determine  the  effect  of  treatments,  data  were  analyzed  with  ANOVA  and  Duncan  test.  The  results showed  that  the mixture of  feces of beef  cattle and horse  feces with various C  / N  ratio had  significant ffect on total bacteria and coliform in sludge. Treatment P3 (C / N ratio 35) to produce the total number of bacteria (4.95 x 107 cfu / g) and coliform (6.33 x 106 cfu / g) the lowest.